The Anglo-Saxon library - Lapidge, Michael (Oxford University Press, 2005)
This invaluable study sets out the evidence for the nature and holdings of libraries in Anglo-Saxon England, from the sixth century to the eleventh. It is furnished with appendices which include editions of all surviving Anglo-Saxon book inventories, lists of those manuscripts exported from and imported into Anglo-Saxon England, and a catalogue of all classical and patristic works cited by Anglo-Saxon authors. The volume is concluded by a comprehensive index (combining the evidence. of inventories, surviving manuscripts, and citations) of all classical and patristic writings known in England b.